Effect of FSMP on Weight Gain in Severely Underweight and Stunted Under-Five Patients - Arda Yunita Subardi; Yunilasari Yunilasari; Yuliana Kusaeri; Anna Maria Nurhajati Widjaja; Nur Nida Fitroh; Prihatini Dini Novitasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Severely underweight in children under five, particularly severely underweight and stunting, remains a major public health issue with long-term impacts on human resource quality. One of the recommended interventions is the provision of Food for Special Medical Purposes (FSMP) in healthcare facilities. This study aimed to determine the effect of the program on weight gain among underweight and stunted under-five patients in the Sakura Inpatient Ward of Bekasi Regional General Hospital. This was a true experimental study with a one-group pretest-post-test design. The sample was obtained through total sampling of all under-five patients aged 0–36 months with severely underweight and stunting who were hospitalized in the Sakura Inpatient Ward from January 2024 to June 2025, totalling 71 patients. Data were analyzed using paired t-tests with a significance level of 5% (α = 0.05). There was an increase in the average body weight among severely underweight children from 5.31 kg to 5.63 kg (Δ = 0.32 kg; p < 0.001), and among those with both severely underweight and stunting from 4.97 kg to 5.34 kg (Δ = 0.37 kg; p < 0.001). The provision of program significantly increased body weight in under-five children with severely underweight, as well as those with combined severely underweight and stunting.